Soluble interleukin-2 receptor in pediatric patients investigated for hemophagocytic lymphohistiocytosis: A single-center, 10-year-long experience - Janković Srđa; Ćazić Marija; Janić Dragana; Lazić Jelena; Rodić Predrag; Krstovski Nada (Srpski Arhiv za Celokupno Lekarstvo, 2023)
Introduction/Objective Hemophagocytic lymphohistiocytosis (HLH) is a severe hyperinflammatory condition characterized by fever, splenomegaly, and cytopenias. Diagnosis of HLH requires at least five of the eight criteria set by the Histiocyte Society and poses a significant challenge to physicians. HLH-2004 criteria include measurement of plasma levels of soluble receptor for interleukin-2 (sIL-2R), an invaluable tool in the diagnosis of HLH, particularly because it can be measured swiftly and inexpensively. Methods We retrospectively analyzed medical records of 45 pediatric patients (28 boys and 17 girls, median age 8.1 years) who were investigated for suspected HLH in University Children’s Hospital in Belgrade, during the period from 2012 to 2022. Results Ten children were diagnosed with HLH, while 35 did not have HLH. All 10 HLH patients had secondary HLH: eight suffered from infection or inflammatory condition, one from an autoimmune disease, and one from malignancy. Level of sIL-2R was above the HLH-2004 cutoff value of 2400 IU/ml in 9/10 patients with HLH (sensitivity 90%) and 9/35 of patients who did not have HLH (specificity 74.2%). Conclusion Soluble IL-2 receptor measurement is valuable in children suspected to have HLH. Sensitivity and specificity of this analysis can be further improved by strict patient selection and a comprehensive diagnostic approach.